DISCORDS OF MOTHER-DAUGHTER BOND IN TONI MORRISON’S SULA - Soman, Chitra; R. , Jinu (International Journal of Psychosocial Rehabilitation, 2020)
Motherhood is the sanctified institution of humankind, and for certain races, its beyond social significance and has the importance of its survival. Toni Morrison is keen on emphasizing this ideology, and her fiction presents the role of mothers and daughters in the sustenance and continuation of race. As a Black American author, Morrison emphasizes this conflict and penetrates the readers into the understanding of solution, which is often Culturally Rooted Sula presents Black mothers from different generations and their daughters. and Toni Morrison presents how the daughters of these new generations are in conflict with their mothers, causing disruption of Afro-American ideology, leading to the displacement of their lineage. This has been the outcome of the ineffectual cultural knowledge of one's own race arising from the defective relationship between Mothers and Daughters.